Improving Writing Skill of the Seventh-Grade Students through Roundtable - Wedayanti, Ni Putu Juwita; Putri Wirastuti, I Gusti Agung; Krismayani, Ni Wayan (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2025)
Speaking is one of the important language skills among reading, listening, and writing skills. By mastering speaking skills, a person can communicate well to convey the information they have to others. However, there are several problems experienced by students in learning English, including student comprehension, grammatical errors, and fluency. The purpose of this study is mainly to determine whether the writing skills of seventh grade students of SMPN 7 Denpasar in the 2024/2025 academic year can be improved through the roundtable technique. This study uses a classroom action research design carried out in two cycles. The required data were collected by providing research instruments: monologue performance tests and structured questionnaires. After the research cycle process, it was found that the roundtable technique was an appropriate teaching technique to improve the subject's writing skills, especially in composing and performing short descriptive monologues. This can be seen from the results of the pre-test, post-test 1 and post-test 2, which showed a significant increase in the subject's writing skills. In addition, this is supported by a structured questionnaire that showed a positive response to the application of the roundtable technique. It can be concluded that the writing skills of class VII students of SMPN 7 Denpasar in the 2024/2025 academic year can be improved by applying the roundtable technique.